The Life Quality of Mothers of Children With Leukemia and its Related Factors - Mohammad Abdi; Robab Mohammadian; Parisa Abbasi; Maryam Asadi; Elham Mohajer; Shahram Piri (Iran University of Medical Sciences, 2019)
Background: Leukemia is the most prevalent cancer in childhood. Mothers are closer to these children than anyone else and play a vital role in caring for them; therefore, studying their life quality is necessary. This study aimed to determine the life quality of mothers of children with leukemia and its related factors.  Methods: This descriptive cross-sectional study was conducted in 2017. A total of 150 mothers of children with leukemia referring to the blood clinic and hematologic ward of Tabriz Children's Hospital were recruited. The samples were selected by convenience sampling method. Data were collected by the World Health Organization Quality of Life (WHOQOL_BREF) and analyzed by t-test, Analysis of Variance (ANOVA) and Pearson's correlation coefficient in SPSS. Results: The Mean±SD score of the mothers' total quality of life was 68.28±19.77. The educational level and occupational status of the mothers and their age were significantly associated with their life quality (P<0.05). Additionally, there were significant relationships between the mothers' quality of life and parents' income, family collaboration, satisfaction with their social status, and satisfaction with marital life (P=0001). Conclusion: Mothers of children with leukemia have a low quality of life, and some of their socio-demographic factors could have a significant effect on their life quality. Therefore, it is suggested that nurse managers introduce vulnerable families to support organizations through appropriate planning. It is also suggested that authorities, by adopting appropriate policies, increase the general knowledge on marital affairs.